Gis "Cities of Russia": Principles of Creation and Technologies of Spatial Analysis - A. A. Cherkasov (Наука. Инновации. Технологии)
Introduction: agglomerated territories are actively investigated by Russian scientists. Mostly, the works are devoted to the role of agglomerations in the sustainable development of territories; administrative, managerial, and town-planning aspects are considered. At the same time, in modern conditions, Russian agglomerations have become attractive for a multi-ethnic migration flow, which leads to a change in the ethnic structure of the population not only in the core cities, but also in suburban areas. This increases interest in the study of ethnic processes in urban agglomerations. The accumulation of new knowledge about the ethnic structure of the population of urban agglomerations, the influence of agglomerated forms of settlement on the formation of the ethnic composition of the peripheral territories, is an urgent task to study the spatial features of the country's population formation, makes a significant contribution to the updating of humanitarian, sociological and socio-geographical studies. Materials and methods of the research: the paper considers the features of the ethnic structure of the population of five urban agglomerations: monocentric- Volgograd GA, Rostov GA, Stavropol GA, Kazan GA, polycentric - GA Mineral Water (CMS). The agglomeration data differ in terms of population, number of urban and rural settlements. In the course of the study, a comparative analysis of the dynamics of the number of agglomerations prevailing in the number of ethnic groups was carried out, the distribution of the second and third ethnic groups, including the comparison for 2002 and 2010, was analyzed by cities and municipal areas. The results of the study and their discussion: features of forming the ethnic structure of the population of the Rostov, Volgograd, Stavropol, Kazan urban agglomeration and the agglomeration of Caucasian Mineral waters are considered. The general trends and regional features of the ethnic structure of the population are revealed. The general tendencies are a decrease in the proportion of Russians and other most urbanized ethnic groups (Ukrainians, Belarusians, Jews, Germans, etc.) and an increase in the number and proportion of ethnic groups with a lower level of urbanization. Conclusions: the study revealed general trends and regional characteristics of the formation of the ethnic structure of the population of urban agglomerations. Common to all agglomerations is the tendency to reduce the proportion of Russians and other, most urbanized ethnic groups (Ukrainians, Belarusians, Jews, Germans, etc.) and the increase in the number and proportion of ethnic groups with a lower level of urbanization.